APPLICATION OF EXPERIMENTAL METHODS TO IMPROVE LEARNING OUTCOMES CLASS V STUDENTS ON SCIENCE LEARNING ABOUT LIGHT PROPERTIES - Nurhidayat, Firman Mauluddin; Riani, Rina; Firdaus, Anugrah Ramadhan (COLLASE (Creative of Learning Students Elementary Education), 2018)
Natural Sciences includes basic natural science that has a lot to do with life and life in this world. That is the background of this research. Learning Natural Sciences has been given since students in elementary school. It is very important for students to understand the process of forming elements of life in the surrounding environment. The results of learning Natural Sciences in the fifth-grade students of SDN 001 Merdeka were still relatively low. In addition, the learning process so far allegedly runs monotonically and can make students feel bored easily, so the classroom atmosphere is no longer conducive to the learning process. Seeing this fact, researchers conducted classroom action research by applying experimental methods to the learning process in the classroom. With the experimental method, it is expected that students will feel interested in learning new things, including fostering curiosity in students about the characteristics of the light they encounter daily. The learning outcomes are also expected to improve better, considering that in the experimental method students can directly gain experience and knowledge directly. The results of this study can also be used as reference material for teachers to conduct further research or similar research.